(untitled) (Journal of Bangladesh Academy of Sciences, 2026)
Azobenzene (AB) and its derivatives exhibit reversible photoisomerization, making them promising candidates for molecular switches and optoelectronic applications. In this study, the electrochemical behavior of AB was investigated in surfactant-based organized media, including micelles, reverse micelles, and microemulsions formed using the cationic surfactant cetyltrimethylammonium bromide (CTAB). UV-visible spectroscopy confirmed the characteristic π-π* electronic transition of AB, while dynamic light scattering measurements revealed nanoscale organization with particle sizes below 10 nm in all media. Cyclic voltammetry showed that the redox behavior of AB is strongly governed by the interfacial environment of the surfactant assemblies. CTAB exhibits characteristic peaks arising from the adsorption/reduction of CTA⁺ at the electrode surface, which overlap with the electrochemical response of AB in micellar media. In contrast, reverse micellar and microemulsion systems exhibit well-defined cathodic ( -0.70 V) and anodic ( 0.25 V) peaks of AB with the interference of CTAB reduction. The results highlight the influence of surfactant-based nanostructures on the electrochemical properties of AB, with a foundation for designing photoresponsive molecular devices with enhanced electrochemical control. J. Bangladesh Acad. Sci. 50(2); 269–281: June 2026